2018
DOI: 10.1002/ece3.4497
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nuchal glands, unusual defensive organs of Asian natricine snakes (Serpentes: Colubridae), inferred from a molecular phylogeny

Abstract: A large body of evidence indicates that evolutionary innovations of novel organs have facilitated the subsequent diversification of species. Investigation of the evolutionary history of such organs should provide important clues for understanding the basis for species diversification. An Asian natricine snake, Rhabdophis tigrinus, possesses a series of unusual organs, called nuchal glands, which contain cardiotonic steroid toxins known as bufadienolides. Rhabdophis tigrinus sequesters bufadienolides from its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 40 publications
9
30
0
1
Order By: Relevance
“…The result showed that R. tigrinus and R. guangdongensis form a sister relationship at the base of the monophyletic system (PP ¼ 1). Similar results showed previous studies (Figueroa et al 2016;Takeuchi et al 2018). This study first revealed the complete mitochondrial genome of…”
supporting
confidence: 91%
“…The result showed that R. tigrinus and R. guangdongensis form a sister relationship at the base of the monophyletic system (PP ¼ 1). Similar results showed previous studies (Figueroa et al 2016;Takeuchi et al 2018). This study first revealed the complete mitochondrial genome of…”
supporting
confidence: 91%
“…Here we report data from five additional specimens that confirm the validity of R. guangdongensis as a member of the "nuchal gland clade" described by Takeuchi et al (2018). Moreover, we dissected two specimens of R. guangdongensis to determine whether this species possesses nuchal or nucho-dorsal glands.…”
Section: Introductionsupporting
confidence: 62%
“…This report of nucho-dorsal glands in R. guangdongensis raises the number of species that possess nuchal glands or nucho-dorsal glands to 18. Rhabdophis guangdongensis was the only species included in the molecular phylogeny of Takeuchi et al (2018) for which the condition of the nuchal glands was not known (Other six species of Rhabdophis lacked both information on their defensive glands and sequence data, and thus were not included in that phylogenetic analysis or ours). Our phylogenetic tree is similar in a number of respects to that of Takeuchi et al (2018), although there are also several important differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species group has undergone a shift from the ancestral diet of amphibians to a diet dominated by earthworms ( Fig. 1B) (6). Members of the R. nuchalis Group are smaller than other Rhabdophis, with less dramatic coloration and a narrower head.…”
Section: Resultsmentioning
confidence: 99%